Characteristics of B-lymphocyte subpopulations in renal transplant recipients - S. V. Zybleva; S. L. Zyblev (Трансплантология (Москва), 2021)
Introduction. The presence of multiple subsets of B-cells with specific regulatory functions capable of modulating inflammatory responses havebeen detected. Most of the studies of Bregs function were carried out in the context of autoimmune and infectious diseases, whereas the objective of this research was to study the characteristics of the main, activated and tolerogenic subpopulations of B lymphocytes in patients who underwent kidney transplantation. Objective. To study the indices of B-lymphocyte subpopulations and determine their role in the development of immunological tolerance after kidney transplantation.Material and methods. We have examined 197 recipients who underwent kidney transplantation. We determined B lymphocyte subpopulation levels (CD19+IgD+CD27+ and CD19+IgD-CD27+) before transplantation, on the 1st, 3rd, 7th and 30th days after the transplantation. Allograft function was assessed on day 7 with the division of patients into two groups: with primary graft function and graft dysfunction.Results and discussion. Significant differences were revealed between the groups of recipients over three months in the following cell subpopulation levels CD19+IgD+CD27+ and CD19+IgD-CD27+. During the first 7 days, lower levels of these subpopulations were associated with satisfactory allograft function. However, by the 90th day after surgery, an increase in CD19+IgD+CD27+ B lymphocytes was noted in the group of patients with graft dysfunction.Conclusions. Low levels of not-switched (CD19+IgD+CD27+) and switched (CD19+IgD-CD27+) memory В lymphocytes in the peripheral blood of kidney transplant recipients are associated with a favorable postoperative course. We have found that on the 3rd post-transplant day, the relative level of non-switched memory B lymphocytes (CD19+IgD+CD27+) exceeding or equal to 11.47%, and the level of switched memory B lymphocytes (CD19+IgD-CD27+) exceeding or equal to 20.74% might predict the development of early renal graft dysfunction with a sensitivity and specificity of 88.40% and 84.30% for the former parameter and of 88.70% and 82.40% for the latter one, respectively.